1994
DOI: 10.2466/pms.1994.79.1.99
|View full text |Cite
|
Sign up to set email alerts
|

Field Sobriety Tests: Are They Designed for Failure?

Abstract: Field sobriety tests have been used by law enforcement officers to identify alcohol-impaired drivers. Yet in 1981 Tharp, Burns, and Moskowitz found that 32% of individuals in a laboratory setting who were judged to have an alcohol level above the legal limit actually were below the level. In this study, two groups of seven law enforcement officers each viewed videotapes of 21 sober individuals performing a variety of field sobriety tests or normal-abilities tests, e.g., reciting one's address and phone number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Perrine et al (1993) found that over 50% of drivers at .00% BAC failed Walk and Turn, and that correlations of Walk and Turn and One Leg Stand with BAC failed to reach significance. Cole and Nowaczyk (1994) reported that experienced police officers judged 46.5% of completely sober subjects videotaped performing psychomotor field sobriety tests to be impaired. O'Keefe (2001) reported that 60% of forensic physicians in Scotland with advanced credentials expressed concern that Walk and Turn and One Leg Stand were too difficult and the grading too stringent.…”
Section: Review Of the Empirical Literaturementioning
confidence: 99%
“…Perrine et al (1993) found that over 50% of drivers at .00% BAC failed Walk and Turn, and that correlations of Walk and Turn and One Leg Stand with BAC failed to reach significance. Cole and Nowaczyk (1994) reported that experienced police officers judged 46.5% of completely sober subjects videotaped performing psychomotor field sobriety tests to be impaired. O'Keefe (2001) reported that 60% of forensic physicians in Scotland with advanced credentials expressed concern that Walk and Turn and One Leg Stand were too difficult and the grading too stringent.…”
Section: Review Of the Empirical Literaturementioning
confidence: 99%
“…Considerable effort has been devoted to developing and calibrating "field sobriety tests" to be applied when a driver or a boater is suspected to be above a legal BAC limit (Grossman et al, 1996;Martin, 1998;McKnight et al, 1999), and there is even a study calibrating a field sobriety test battery to measure a BAC level of 0.8 per mille rather than 1.0 per mille (Stuster & Burns, 1998). There are, however, also some more pessimistic reports in this literature (Cole & Nowaczyk, 1994).…”
Section: Previous Studies Of the Relation Of Clinical Assessment To Bmentioning
confidence: 99%
“…To bridge this knowledge gap, an apparatus modeled after a horizontally placed ladder was designed. While this apparatus design may appear to be similar to the “elevated ladder beam” test employed with rats ( Soblosky et al, 1997 ) and mice ( Cummings et al, 2007 ), the design of the Horizontal Ladder Test (HLT) used here drew inspiration from the human standardized field sobriety test (FST), specifically the ‘walk and turn’ test (WAT) utilized for detecting driving under the influence (DUI) of alcohol ( Cole and Nowaczyk, 1994 ; Burns, 2003 ). In the DUI detection test, individuals are instructed to take nine heel-to-toe steps along a straight line, followed by turning on one foot and returning in the opposite direction ( Downey et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%